2020
DOI: 10.1016/j.gaitpost.2020.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Using the spring-mass model for running: Force-length curves and foot-strike patterns

Abstract: Background: The spring-mass model is commonly used to investigate the mechanical characteristics of human running. Underlying this model is the assumption of a linear force-length relationship, during the stance phase of running, and the idea that stiffness can be characterised using a single spring constant. However, it remains unclear whether the assumption of linearity is valid across different running styles.Research question: How does the linearity of the force-length curve vary across a sample of runners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…This result corroborates the choice made by several authors to use the decompression phase instead of the compression one to calculate the vertical stiffness (Cavagna et al, 1988;Schepens et al, 1998). Deviation from linearity of the force-length relationship among individuals was also reported by Gill et al (2020). Indeed, these authors reported that the linearity of the force-length curve was foot-strike index (foot-strike pattern) dependent and that this curve should be investigated before using the spring-mass model.…”
Section: Figuresupporting
confidence: 85%
See 3 more Smart Citations
“…This result corroborates the choice made by several authors to use the decompression phase instead of the compression one to calculate the vertical stiffness (Cavagna et al, 1988;Schepens et al, 1998). Deviation from linearity of the force-length relationship among individuals was also reported by Gill et al (2020). Indeed, these authors reported that the linearity of the force-length curve was foot-strike index (foot-strike pattern) dependent and that this curve should be investigated before using the spring-mass model.…”
Section: Figuresupporting
confidence: 85%
“…The spring-mass characteristics of the lower limb were assessed by computing the force-length relationship ( Gill et al, 2020 ), i.e., the force vector projected along the leg as function of the leg compression/decompression during stance, and ( Liew et al, 2017 ), calculated using both the compression and decompression of the human body ( Gill et al, 2020 ) and adapted from Liew et al (2017) . More explicitly, compressive ( k leg, comp ) and decompressive ( k leg, decomp ) leg stiffnesses were given by the maximum of the force vector projected along the leg ( F leg,max ) divided by the maximum leg compression ( ∆L comp ) and decompression ( ∆L decomp ) during stance, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the mechanical stiffness during braking and propulsion phases does not necessarily have to be the same. To understand the phenomena occurring during running tasks, it seems necessary to determine the mechanical stiffness for both these phases separately [ 154 , 155 ]. Such an approach has been used in a number of studies, although these approaches differ.…”
Section: Resultsmentioning
confidence: 99%